1995
DOI: 10.1074/jbc.270.7.3234
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase 1 Subunits with Mutations Linked to Familial Amyotrophic Lateral Sclerosis Do Not Affect Wild-type Subunit Function

Abstract: Mutations in superoxide dismutase 1 (SOD1) have been linked to familial amyotrophic lateral sclerosis, a dominantly inherited motor neuron disorder of midlife. Because SOD1 is a homodimeric enzyme, dimerization of mutant and wild-type SOD1 subunits could dominantly alter the activity, stability, or localization of wild-type SOD1 subunits. To explore these possibilities, we used transient and stable gene transfection to express high levels of either of two mutant human SOD1 subunits in the presence of limited l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
85
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(87 citation statements)
references
References 25 publications
2
85
0
Order By: Relevance
“…Several studies have shown that expression of mutant SOD1 exerts toxic effects on cultured cells (11,12). We investigated the biological effects of RNAi-mediated silencing of SOD1 in a mouse neuroblastoma (N2a) cell line that constitutively expresses high levels of FALS-linked mutant human SOD1 (SOD1 G37R ) (12,32). In this system, overexpression of SOD1 G37R does not affect cell viability under normal culture conditions but renders cells more sensitive to cytotoxic stimuli (12).…”
Section: Functional Analysis Of Rnai-mediated Silencing Of Mutant Sod1mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that expression of mutant SOD1 exerts toxic effects on cultured cells (11,12). We investigated the biological effects of RNAi-mediated silencing of SOD1 in a mouse neuroblastoma (N2a) cell line that constitutively expresses high levels of FALS-linked mutant human SOD1 (SOD1 G37R ) (12,32). In this system, overexpression of SOD1 G37R does not affect cell viability under normal culture conditions but renders cells more sensitive to cytotoxic stimuli (12).…”
Section: Functional Analysis Of Rnai-mediated Silencing Of Mutant Sod1mentioning
confidence: 99%
“…HeLa cells were maintained in DMEM supplemented with 10% heat-inactivated FBS, 2 mM L-glutamine, 100 units͞ml penicillin, and 100 g͞ml streptomycin. Neuro-2a (N2a) murine neuroblastoma cell lines stably expressing human mutant SOD1 G37R (12,32) were maintained in DMEM supplemented with 7% FBS, 2 mM Lglutamine, and 400 g͞ml G418. DNA and siRNA transfections were performed with Lipofectamine 2000 (Invitrogen) according to the manufacturer's recommendations and published procedures (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 10% of ALS cases are familial [1], and about 20% of the familial amyotrophic lateral sclerosis (FALS) cases have mutations in SOD1, the gene that encodes the human Cu,Zn-superoxide dismutase (SOD) [2]. Several studies reported that Cu,Zn-SOD mutants retained high levels of dismutation activity [3][4][5][6], which suggests that the FALS mutations in SOD1 may act through a dominant cytotoxic gain-of-function [3][4][5][6][7]. The mouse models of FALS that overexpressed the mutant human Cu, Zn-SOD suggested that the gain-of-function of the Cu,Zn-SOD contributed to the pathophysiology of FALS [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies with transgenic mice (8,21), transfected cells (22,23), and lymphoblasts of patients (24) revealed that levels of total Cu,Zn-SOD dismutation activities remain high or higher than normal, which suggests that the FALS mutations in SOD1. may act through a dominant cytotoxic gain-of-function (8,(21)(22)(23)(24). We investigated whether there are any differences in the free radical-generating function between the wild-type and FALS mutant Cu,Zn-SOD.…”
mentioning
confidence: 99%